The nitrovinyl moiety determines the cyto- and genotoxic profiles of β-nitrostyrene derivatives: evidence from in silico and in vitro evaluation - Jan Sündermann; Stella Marie Reamon-Buettner; Sabrina Wilde; Annette Bitsch; Christina Ziemann (Archives of Toxicology, 2026)
β-Nitrostyrene, an important intermediate in chemical industry, shows relevant anti-proliferative and pro-apoptotic potential and has thus been suggested for potential use in tumor chemotherapy. If not derivatized, β-nitrostyrene is however, highly reactive and possess (geno)toxic potential. To decipher structural elements relevant for biological activity, crucial for both, chemical risk assessment and potential drug development, a panel of nine structural derivatives of β-nitrostyrene, was put together. It included structures with and without nitrovinyl moiety and was based on fingerprint similarity, QSAR-based mutagenicity alerts, and literature reports. It comprised simple structures like styrene and more complex structures such as 2-methoxy-5-[(E)-2-nitroethenyl]phenol. In vitro experiments in human WS1 and mouse L5178/TK ± cells demonstrated that the nitrovinyl moiety of β-nitrostyrene seems vital for its cytotoxic (membrane damage, metabolic competence) and genotoxic (clastogenicity, mutagenicity) properties. The extent of adversity varied with modification of structural elements. For example 1-nitro-2-[(E)-2-nitroethenyl]benzene led to 2.3-fold higher mean tail intensities in the alkaline comet assay than β-nitrostyrene. Notably, all derivatives with a nitrovinyl moiety, except 5-[(E)-2-nitroethenyl]-1,3-benzodioxole, induced DNA double-strand breaks, as judged by γH2A.X induction. In conclusion, our study identified structural elements responsible for the cyto- and genotoxic potential of β-nitrostyrene, demonstrating that minor structural changes can significantly alter its adverse biological activity.

Oil mists and vapours: A review of exposure and toxicity, with dose descriptors from inhalation studies - Niels Hadrup; Jorid B. Sørli; Marie Frederiksen; Anoop K. Sharma; Sabine Kafert-Kasting; Sven Schuchardt; Annette Bitsch; Per A. Clausen; Anne Thoustrup Saber; Ulla Vogel; Karin S. Hougaard (Toxicology, 2026)

Methodological steps forward in toxicological in vitro screening of mineral wools in primary rat alveolar macrophages and normal rat mesothelial NRM2 cells - Christina Ziemann; Florian Schulz; Christoph Koch; Mette Solvang; Annette Bitsch (Archives of Toxicology, 2024)
Man-made vitreous fibers (MMVF) comprise diverse materials for thermal and acoustic insulation, including stone wool. Depending on dimension, durability, and dose, MMVF might induce adverse health effects. Therefore, early predictive in vitro (geno)toxicity screening of new MMVF is highly desired to ensure safety for exposed workers and consumers. Here, we investigated, as a starting point, critical in vitro screening determinants and pitfalls using primary rat alveolar macrophages (AM) and normal rat mesothelial cells (NRM2). A stone wool fiber (RIF56008) served as an exemplary MMVF (fibrous vs. ground to estimate impact of fiber shape) and long amosite (asbestos) as insoluble fiber reference. Materials were comprehensively characterized, and in vivo-relevant in vitro concentrations defined, based on different approaches (low to supposed overload: 0.5, 5 and 50 µg/cm 2 ). After 4–48 h of incubation, certain readouts were analyzed and material uptake was investigated by light and fluorescence-coupled darkfield microscopy. DNA-strand break induction was not morphology-dependent and nearly absent in both cell types. However, NRM2 demonstrated material-, morphology- and concentration-dependent membrane damage, CINC-1 release, reduction in cell count, and induction of binucleated cells (asbestos > RIF56008 > RIF56008 ground). In contrast to NRM2, asbestos was nearly inactive in AM, with CINC-1 release solely induced by RIF56008. In conclusion, to define an MMVF-adapted, predictive in vitro (geno)toxicity screening tool, references, endpoints, and concentrations should be carefully chosen, based on in vivo relevance, and sensitivity and specificity of the chosen cell model. Next, further endpoints should be evaluated, ideally with validation by in vivo data regarding their predictivity.

Is read-across for chemicals comparable to medical device equivalence and where to use it for conformity assessment? - Jan Sündermann; Annette Bitsch; Rupert Kellner; Theodor Doll (Regulatory Toxicology and Pharmacology, 2024)

The life of Hans-Günter Neumann and his contributions to chemical carcinogenesis - Manfred Metzler; Annette Bitsch; Gisela H. Degen (Archives of Toxicology, 2020)

Towards grouping concepts based on new approach methodologies in chemical hazard assessment: the read-across approach of the EU-ToxRisk project - Sylvia E. Escher; Hennicke Kamp; Susanne H. Bennekou; Annette Bitsch; Ciarán Fisher; Rabea Graepel; Jan G. Hengstler; Matthias Herzler; Derek Knight; Marcel Leist; Ulf Norinder; Gladys Ouédraogo; et al. (Archives of Toxicology, 2019)